2002
DOI: 10.1002/ajim.10042
|View full text |Cite
|
Sign up to set email alerts
|

Follow‐up study of respiratory health of newly‐hired female cotton textile workers

Abstract: These results suggest that the occurrence of respiratory symptoms represents the earliest response to cotton dust exposure, followed by lung function changes. Early respiratory symptoms may be a risk factor for subsequent loss of pulmonary function in cotton textile workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 20 publications
2
18
0
Order By: Relevance
“…These results correspond to findings of other studies reporting associations of cross-shift lung function changes with the level of endotoxin exposure (Kennedy et al 1987;Wang et al 2002Wang et al , 2003Schwartz et al 1995;Zock et al 1998;Christiani et al 2001;Torres et al 2004). In 1998, Zock et al examined 61 employees of a potato-processing factory; highly exposed subjects tended to have lower lung function variables than those with lower endotoxin exposure (FEV 1 95 vs. 102% predicted).…”
Section: Discussionsupporting
confidence: 95%
“…These results correspond to findings of other studies reporting associations of cross-shift lung function changes with the level of endotoxin exposure (Kennedy et al 1987;Wang et al 2002Wang et al , 2003Schwartz et al 1995;Zock et al 1998;Christiani et al 2001;Torres et al 2004). In 1998, Zock et al examined 61 employees of a potato-processing factory; highly exposed subjects tended to have lower lung function variables than those with lower endotoxin exposure (FEV 1 95 vs. 102% predicted).…”
Section: Discussionsupporting
confidence: 95%
“…Our results indicate that workers currently smokers and occupationally exposed to lignite dust have reported a notable high prevalence of respiratory symptoms. The presence of respiratory symptoms could represent an early biological response to smoking and occupational exposures; thus, it could be a risk factor for loss of pulmonary function in the future 15) . Logistic regression analysis confirmed that occupational exposure to dust was an independent predictor of the occurrence of respiratory symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies from China have recently reported on both symptoms and lung function changes occurring in populations of newly exposed naive cotton workers. 2, 3 We proposed to study the acute effects of first exposure to cotton dust in a Turkish population. The cotton mills selected for this study had a history of a high labor turnover and were situated in an area of rela-…”
mentioning
confidence: 99%